The evolution and convergence of OECD tax systems - Johannes Becker; May Elsayyad (Intereconomics, 2009)
This paper considers theory-based expectations on the evolution of tax structures in developed countries and confronts them with stylised facts from aggregate tax revenue data. A bilateral similarity index is introduced which allows the measurement of the similarity of tax systems conditional on country characteristics. A slow but steady convergence in tax revenue structures is found which depends on the proximity, similarity and exchange between a given pair of countries.
Keywords: 330